Variation in body weight and feed intake trajectories are promising resilience indicators in Texel lambs - Barchet, Fernanda; Ciappesoni, Gabriel; Brito, Luiz F.; De Barbieri, Ignacio (Frontiers in Animal Science, 2025)
IntroductionResilient animals are capable of coping with environmental perturbations or quickly returning to unperturbed performance trajectory after facing challenges. More resilient animals tend to have better welfare, health, and productivity under variable conditions. However, trade-offs between production and resilience traits have been reported, indicating the need for further research to enable genetic selection for increased productive efficiency while maintaining or improving general resilience.MethodsIn this study, data from 76 Texel lambs monitored during a 53-day feed efficiency trial were used to generate 24 indicators of resilience based on variability in daily feed intake (FI), feeding behavior and average daily gain (ADG) and assess their phenotypic relationship with ADG and residual FI (RFI). Some traits evaluated included adgVar (residual variance of ADG), adgLnVar (log-variance of deviation between observed absolute and expected ADG), QRfi (quantile regression of FI), and QRdurfi (quantile regression of duration with effective consumption).ResultsStrong associations were found between indicators, such as adgVar and adgLnVar (r = 0.81). Productive traits showed two clear patterns, ADG was favorably correlated with QRdur (r = -0.53), QRdurfi (r = -0.65), QRfi (r = -0.65), suggesting that more resilient animals tend to have higher ADG. Conversely, RFI presented unfavorable correlations with resilience, ranging from r = -0.46 for QRfi to r = -0.24 for QRtimesfi indicating that more feed-efficient animals may be less resilient.DiscussionThese contrasting results highlight two key findings: (1) productivity and resilience can be favorably associated, as shown by ADG-resilience correlations, however, (2) specific feed efficiency indicators (e.g., RFI) may have antagonistic relationships with resilience. Given the relatively small sample size (n = 76) in this exploratory study, findings should be interpretated with caution but can provide some insights into the relation between resilience and production and potential trade-offs warranting further investigation.